Aplicação de simulação termodinâmica na determinação da viscosidade da escória líquida e na avaliação do comportamento de solidificação de pós fluxantes sem flúor para aços peritéticos - Mendes, Matheus Rodrigues (2022)
The addition of fluoride to mold fluxes results in several beneficial effects, such as improvement of melting and viscosity properties and control of heat transfer in the mold by cuspidine precipitation. The control of heat transfer by the formation of cuspidine has fundamental importance in the production of steels with medium carbon content, preventing the formation of longitudinal cracks. Despite the benefits mentioned, the presence of fluoride can cause damage to the environment and the health of the plant operators, besides causing corrosion of the equipment. Due to this fact, several researchers have been working in the search for alternative, more suitable, components to replace fluoride. In this task, the use of computational tools and experimental validation has been shown to be an efficient method in optimizing the process of elaborating new compositions. Thus, the aim of this study was to evaluate the effect of varying the content of the components Na2O, B2O3 and TiO2 – which stand out as the most promising in fluoride substitution – by means of thermodynamic equilibrium simulations. With the help of FactSage tool, the liquidus temperature, viscosity and phases formed during the solidification of the slag with the compositions of interest were evaluated. Simulation results have shown good correspondence with the experimental data available in the literature.